Weight gain in the first two years of life, asthma and atopy: the SCAALA cohort study - Matos, Sheila Maria Alvim de (2013)
Objective: To evaluate the association between weight gain in the first two years of life and the occurrence of wheezing, asthma, serum IgE, skin reactivity and pulmonary function. Design: Cohort study. Setting: The metropolitan region of Salvador, Bahia, Brazil. Subjects: The association was studied between 1997 and 2005 in 669 children up to 11 years of age. Data were collected on asthma and risk factors, both current factors and those present in the first years of life. Weight gain was considered fast when the Z-score was .0?67. Poisson regression was used in the multivariate statistical analysis. Results: Wheezing was reported in 25?6% of the children. Weight gain was considered fast (Z-score .0?67) in 29?6% of the children and slow (Z-score,20?67) in 13?9%. Children in the slow weight gain group had 36% fewer symptoms of asthma (prevalence ratio50?65; 95% CI 0?42, 0?99). Conclusions: Slower weight gain in the early years of life may constitute a protective factor against symptoms of asthma. The relevance of this finding for public health is not yet certain, since it is known that children with slow and fast weight gain may be more likely to develop adverse health consequences related to both these situations.